'The golden era' of Finnish documentary film financing and production. Issue 2 (3rd May 2016) - Haase, Antti
ABSTRACT: This article outlines trends in Finnish documentary film industry during the so-called golden era of 1990s and early 2000s based on key variables in documentary film financing and production. This period coincides with global documentary financiers increasing market orientation ('factual turn', which has largely broken the ties of documentary film production with filmic modes of craftsmanship and public service [Hogarth 2006. Realer than Real: Global Directions in Documentary . Austin: University of Texas Press, 5]. Public service cinema culture was still largely intact in Finland in the early 2000s and is the main reason for the 'golden era'. The 'golden era' would not have been possible without strong domestic public subsidy organizations, The Promotion Centre for Audiovisual Culture (Audiovisuaalisen kulttuurin edistämiskeskus, or AVEK) and the Finnish Film Foundation (Suomen elokuvasäätiö, or SES). Another crucial factor is that the Finnish Broadcasting Company (YLE) has not given in to the global 'factual turn'. Finnish documentary filmmakers strongly identify with Aaltonen's [2006. Todellisuuden vangit vapauden valtakunnassa: Dokumenttielokuva ja sen tekoprosessi [The Prisoners of Reality in the Realm of Freedom: Documentary Film and Its Production Process]. Keuruu: Like, 248] observation that the metanarrative of documentary film is the narrative of itself becoming an art.